2021
DOI: 10.1007/s42452-021-04365-2
|View full text |Cite
|
Sign up to set email alerts
|

AgNPs@ZnO hybride nanoparticles infused thermoplastic polyester elastomer and their biocide effect

Abstract: This paper presents research results of biocidal effect of thermoplastic- polyester-elastomer (TPE-E) with incorporation of hybrid Ag/ZnO/SiO2 NPs (silver/Zinc oxide/SiO2 nanoparticles). These results were compared with various gamma-irradiated doses and processing techniques including extrusion, injection molding and compression molding. In all these processing techniques the TPE-E was mixed with mineral oil and Ag/ZnO/SiO2 nanoparticles. The TPE-E nanocomposites were characterized by differential scanning ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…It was found that the PET S-AgNPs had antimicrobial activity on both gram-negative and gram-positive bacteria [ 23 ]. The number of applications for AgNPs increases exponentially, including nanosilver in association with other metallic nanoparticles [ 24 ]. With this, the search for new antimicrobial and antiviral materials becomes timely and eminet, including in the fight against Covid 19 [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the PET S-AgNPs had antimicrobial activity on both gram-negative and gram-positive bacteria [ 23 ]. The number of applications for AgNPs increases exponentially, including nanosilver in association with other metallic nanoparticles [ 24 ]. With this, the search for new antimicrobial and antiviral materials becomes timely and eminet, including in the fight against Covid 19 [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, countless cases of diseases that are associated with foodborne pathogens are reported every year worldwide [ 44 ]. Biocide materials covered by polymers is an important strategy to be applied for different uses, what makes the studies of possible food storage packaging viable and promising because they can inhibit the growth of microorganisms and food spoilage, extending the product a longer shelf life [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of dispersant or surfactant [33]; • Mechanical mixing during the extrusion process for thermoplastic polymers [34]; • Sonication to break down agglomerates and ensure proper dispersion [35];…”
mentioning
confidence: 99%